Lecturers’ and Students’ Perceptions on Online Assessment in Offline Science Courses in Higher Education in South-East Geo -Political Zone, Nigeria - Amaka Okoye; Ijeoma I. Chikezie (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study investigated lecturers’ and students’ perceptions of online assessment in science courses traditionally taught offline in higher institutions across South-East Nigeria. A quantitative descriptive survey design was adopted, guided by three research questions and three hypotheses. Using a multi-stage sampling technique, 62 lecturers and 379 students were selected from three states. Data were collected using two validated instruments, LPOAOCQ and SPOAOCQ, with reliability coefficients of 0.771 and 0.723 respectively, administered via Google Forms. Descriptive statistics, independent t-tests, and ANOVA were used for analysis at a 0.05 significance level. Results showed no significant difference between lecturers’ and students’ overall perceptions. However, while lecturers’ views did not vary significantly by gender or qualification, students’ perceptions differed significantly by gender and age, but not by academic level. The findings highlight challenges in assessing psychomotor skills through online formats, especially in science education where hands-on activities are essential. The study emphasizes the need for authentic, context-rich assessments that reflect real-world scientific practice. It was recommended among others that Institutions should adopt blended assessments that integrate online tools with hands-on evaluations to effectively measure student competencies.